METODOLOGI TRANSMISI KEILMUAN ISLAM KLASIK Upaya Reaktualisasi Metodologi Pengajaran - Fahri, Ismail (Universitas Negeri Semarang, 2008)
To preserve the past inheritance is a task for our next generation. Recorded inhistory, classic Muslims has bequeathed prosperity and glory. One of the examples iseducation. The progress of Muslim education is supported by many factors. One ofthem is teaching method. The good teaching method of course will produce generationwhich has a certain quality. Historically, teaching method of classic Muslim hasbrought the advance and fragrance toward Muslim in other countries' eye in the world.But, the past victory is just only a beautiful memory because the next generationcannot able to preserve classic culture. Teaching method becomes a problem since thatmethod does not have influence in developing personality and intellectual quality.Teaching method in institute of Muslim education still oriented on the conventionalmethod. The material delivery is dominated by speech method or